2011
DOI: 10.1007/s10682-011-9519-1
|View full text |Cite
|
Sign up to set email alerts
|

Wild yellow dung fly females may not select sperm based on dung pat microclimate but could nevertheless benefit from polyandry

Abstract: Molecular techniques have substantially improved our knowledge of postcopulatory sexual selection. Nevertheless, studies examining sperm utilization in natural populations of nonsocial insects are rare, support for sperm selection (biased use of stored sperm, e.g. to match offspring genotypes to prevailing environmental conditions) is elusive, and its relevance within natural populations unknown. We performed an oviposition site choice experiment in the field where female yellow dung flies Scathophaga stercora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
(65 reference statements)
2
18
0
Order By: Relevance
“…(), and Demont et al. (). Table additionally provides information on the sample sizes, the number of alleles, and the mean observed ( H O ) and expected ( H E ) heterozygosity for each locus across North America, Europe, and Japan.…”
Section: Methodsmentioning
confidence: 97%
“…(), and Demont et al. (). Table additionally provides information on the sample sizes, the number of alleles, and the mean observed ( H O ) and expected ( H E ) heterozygosity for each locus across North America, Europe, and Japan.…”
Section: Methodsmentioning
confidence: 97%
“…They concluded that although pgm activity differences were apparent, and that pgm genotype did differentially affect development time, eggs laid on the north versus south slopes showed no biases in pgm composition as indicated from the previous work, removing the basis for cryptic female choice of sperm with different pgm genotypes. Further, Demont et al (2012) performed field experiments in which females could choose to lay eggs in three different dropping microenvironments (south slope, ridge, and north slope), and genotyped both (i) the resulting offspring, and (ii) the sperm remaining in the female sperm stores after oviposition. Although (as expected) females showed a greater preference to oviposit on north slopes as ambient temperature increased, they found no evidence that females biased paternity towards certain male genotypes depending on the offspring's microclimate.…”
Section: Studies On Sperm Selection By Femalesmentioning
confidence: 99%
“…Differential sperm storage and usage has been repeatedly demonstrated in S. stercoraria using phenotypic or molecular markers (Otronen, Reguera & Ward ; Hellriegel & Bernasconi ; Bussière et al . ; Demont, Martin & Bussière ). Since artificial selection for expressing 4s induced fecundity costs in female S. stercoraria , potential mate choice benefits could trade‐off against costs that females incur from producing an additional sperm storage compartment (Ward ; Ward, Wilson & Reim ).…”
Section: Introductionmentioning
confidence: 99%